Kajian Pustaka: Kualitas Minuman Probiotik Berbahan Dasar Nabati dengan Variasi Sukrosa dan Bakteri Asam Laktat - Rahmawati, Felicia Desi Nora; Swasti, Yulia Reni; Purwijantiningsih, Ekawati (Program Studi Teknologi Pangan, 2020)
Probiotics which are generally recognized by the public are processed using cow’s milk as the basic ingredient, which is relatively expensive. Diversification of vegetable ingredients into an alternative to milk as a basic ingredient for probiotics that is processed in a modern way with the aim the product can be consumed by the wide community at a more affordable price. The development of plant-based probiotics processing refers to the various nutritional content of vegetable ingredients and the use of vegetable ingredients of less value in an area. Vegetable ingredients such as fruits and vegetables have good nutrition so that materials are suitable as a medium for growth of lactic acid bacteria. Probiotic supplements that are widely used as a starter for probiotics come from genus Lactobacillus and Bifidobacterium. Feasibility and consumption standard based on chemical, physicochemical, microbiological, and organoleptic parameters are influenced by treatment during the processing of probiotics such as sugar supplementation and variations of probiotic supplements. Application of vegetable materials as a substrate for lactic acid bacteria and treatment during processing determines the final quality of the probiotics product.